The unequal burden of poverty on time use - Burca Kizilirmak; Emel Memis (Levy Economics Institute of Bard College, 2009)
This study uses the first time-use survey carried out in South Africa (2000) to examine women's and men's time use, with a focus on the impacts of income poverty. We empirically explore the determinants of time spent on different paid and unpaid work activities, including a variety of household and individual characteristics, using bivariate and multivariate Tobit estimations. Our results show asymmetric impacts of income poverty on women's and men's time use. Time-use patterns of South African women and men reveal the unequal burden of income poverty among household members. While being poor increases the amount of time women spend on unpaid work, we do not see any significant impact on men's unpaid work time. For example, women in poor households spend more time than men collecting water and fuel, as well as maintaining their homes.
Keywords: D31; D63; 330; unpaid work; time use; gender-based inequality